A review of minimally invasive fracture stabilization in dogs and cats. (26th July 2021) - Pozzi, Antonio; Lewis, Daniel D.; Scheuermann, Logan M.; Castelli, Emanuele; Longo, Federico
Abstract: Objective: To summarize and discuss peer‐reviewed studies on minimally invasive osteosynthesis (MIO) of long bone, physeal, and articular fractures in dogs and cats. Study Design: Invited review. Methods: A critique of literature was performed to assess MIO feasibility, outcomes, and complications through PubMed, Scopus, and CAB abstracts research databases (2000–2020). Results: More than 40 MIO articles have been published in the last 15 years, but most studies had small numbers, lacked control groups, and used limited outcome measures. Studies generally showed that MIO was feasible in dogs and cats with low complication rates. The current evidence does not demonstrate superior bone healing or functional outcomes with MIO when compared to standard methods. Although treatment principles, case selection, and techniques varied depending on the anatomical location, there were no salient differences in complication rates among long bones, physeal, and articular fractures treated by MIO. Conclusion: The current available evidence and the personal experience of the authors support MIO as a promising fracture management modality. MIO can yield excellent outcomes when applied in carefully selected cases, performed by surgeons experienced in the technique. We cannot, however, conclude that MIO is superior to open fracture stabilization based on the available evidence in veterinary literature. Randomized controlled studies are warranted to prospectively compare MIO with other osteosynthesis techniques and thereby validate its role in fracture management for dogs and cats.